Mobile caecum as a content in recurrent incisional hernia an incidental finding: A rare case report. (April 2021) - Hariprasad, Chinniahnapalaya Pandurangaiah; Gupta, Rohit; Kumar, Anil; Jha, Deepak Kumar; Kishor, Shiv; Paswan, Shiv Shankar
Highlights: Mobile caecum as a content of hernial sac in recurrent incisional hernia is a very rare entity. As per the available literature this is the first case of mobile caecum as content of recurrent incisional hernial. Caecopexy using the lateral peritoneal flap is the treatment of choice for mobile caecum. Abstract: Introduction: Recurrence in ventral hernia after laparoscopic repair is less as compared to conventional approach. Mobile caecum as a content of ventral hernia is a very rare entity. Standard treatment for mobile cecum is caecopexy using lateral peritoneal flap. Case report: A 40-year-old obese female, homemaker by occupation with a history of incisional hernia 2 year back and treated with intraperitoneal on lay mesh repair presented with swelling in the left lower abdomen for past 6 months. Radiological investigations revealed defect in left lower anterior abdominal wall with protruding bowel loops. Urgent exploratory Laparotomy revealed mobile segment of ileocecal junction in the hernial sac cavity. Caecopexy for the mobile caecum was done. Discussion: Mobile caecum is due to embryological failure of fusion of right colonic mesentery with lateral peritoneal wall. Pre-operative diagnosis of mobile caecum is difficult to establish unless it presents as caecal volvulus Caecopexy using the lateral peritoneal flap is the standard of care. Conclusion: Mobile caecum can surprise the attending surgeon as a content of ventral hernia. Caecopexy using lateral peritoneal flap is the treatment of choice in all with a mobile caecum.